Investigating the influence of Beteri’s social intelligence in ‘Andai-andai’ folktales on societal perspectives - Junaidi, Febi; Rahmanto, Andi Adam; Fitriana, Eka; Ni'matussyahara, Dannis; Damayanti, Ariska; Riyanti, Ratnasari Dwi; Sunardy (Research Journal in Advanced Humanities, 2024)
The purpose of this study is to describe the values of social intelligence associated with the character of Beteri in folktales of Kedurang, Bengkulu, and to explore the community’s perspectives about Beteri. Researchers collected folktales featuring Beteri, conducted interviews with informants, and analyzed the contents of the collected folktales to identify the values of social intelligence within them. The analyzed stories featuring various Beteri characters are Beteri and Sinamnam, Beteri and Bujang Bekurung, and The Kindness of Beteri. The results revealed that the social intelligence depicted in the story of Beteri encompasses two main dimensions: social awareness and social facilities. Researchers identified representations of social intelligence in the story, including caring, alignment, empathic accuracy, influence, and social cognition. This social intelligence is manifested in Beteri’s actions during interactions with other characters and her attitude when facing problems. Findings from observations and interviews also indicate that people consider Beteri to be a model virtue, being described as a very good girl.